Shaping Security Beyond Arms: The Quad and Human Futures in the Indo-Pacific - Parfej Ali; Salil Biswas (Faculty of Social and Political Science, 2025)
In contemporary world politics non-traditional security is a major concern, which is unlike preceding centuries. Numerous non-state actors such as terrorist networks, drug cartels, civil wars, and maritime piracy networks known as new age threats. Apart from such non-traditional non-state and transnational security threats environmental degradation is a gravest threat to the future existence of the modern sovereign entities. Whereas non-traditional security is closely related to human security i.e. human security is a core component or lens through which (non-traditional security) NTS is understood and addressed. In 2004 Quad were established to coordinate humanitarian assistance and disaster relief in Indian Ocean Tsunami. The Quad’s regional strategy has evolved from a purely strategic-security framework to one that prioritizes human-centric concerns. By addressing health, climate resilience, disaster relief, and digital empowerment, the Quad is aligning its policies with the principles of human security, thus broadening its influence as a multilateral platform committed to inclusive, sustainable development in the Indo-Pacific. Therefore, this study is being conducted through qualitative research method, and the research design are descriptive and analytical based on secondary data, this paper aims to explore the intricate linkages between non-traditional security challenges and the evolving role of the Quad in shaping a human-centric strategy for the Indo-Pacific region.